2009
DOI: 10.1073/pnas.0901767106
|View full text |Cite
|
Sign up to set email alerts
|

Netrin-1 up-regulation in inflammatory bowel diseases is required for colorectal cancer progression

Abstract: Chronic inflammation and cancer are intimately associated. This is particularly true for inflammatory bowel diseases (IBD), such as ulcerative colitis and Crohn's disease, which show a major increased risk for colorectal cancer. While the understanding of the molecular pathogenesis of IBD has recently improved, the mechanisms that link these chronic inflammatory states to colorectal cancer development are in large part unknown. One of these mechanisms is NF-B pathway activation which in turn may contribute to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
117
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 108 publications
(121 citation statements)
references
References 24 publications
3
117
0
1
Order By: Relevance
“…New perspectives are currently arising, consisting in characterizing tumors that express both a dependence receptor and its ligand and trying to interfere with production of the latter. [38][39][40][41] We provide strong evidences supporting an evolutionary acquisition of dependence behavior for Krm1, which might be one of the mechanisms by which placental mammals tackled the necessity to develop protective strategies against cancers. We further suggest that in humans, Krm1 apoptotic behavior can be regulated by alternative splicing.…”
Section: Discussionmentioning
confidence: 63%
“…New perspectives are currently arising, consisting in characterizing tumors that express both a dependence receptor and its ligand and trying to interfere with production of the latter. [38][39][40][41] We provide strong evidences supporting an evolutionary acquisition of dependence behavior for Krm1, which might be one of the mechanisms by which placental mammals tackled the necessity to develop protective strategies against cancers. We further suggest that in humans, Krm1 apoptotic behavior can be regulated by alternative splicing.…”
Section: Discussionmentioning
confidence: 63%
“…Moreover, according to the well-admitted link between inflammation and colorectal cancer predisposition, it has been suggested that nuclear factor-kB activation resulting from inflammatory stimulus could lead to local netrin-1 production, and thus to tumor promotion by apoptosis inhibition. Along this line, colorectal tumor formation in an animal model for chronic inflammation was inhibited by treatment with netrin-1 titrating agents (Paradisi et al, 2009). …”
Section: Drs Are Altered During Tumor Progressionmentioning
confidence: 99%
“…Moreover, the biologic has a dramatic effect on tumor progression, as it triggers an increased frequency of low grade adenoma associated with a decreased incidence of high-grade adenoma and adenocarcinoma. 23 The effect of netrin-1 inhibition in inflammationdriven tumorigenesis is quite similar to the specific ablation of IKKβ in IECs, with some difference: the effect of the netrin-1 blocking agent in tumor promotion (i.e., number of tumors) is modest, as compared to enterocyte-IKKβ knockout mice, indicating a partial inhibition of pre-malignant cell apoptosis by netrin-1. The mild effect of netrin-1 inhibition in tumor promotion was quite expected, as netrin-1 is not the only survival factor dependent on NFκB activation.…”
Section: Discussionmentioning
confidence: 83%
“…22 In AOM/DSStreated mice, netrin-1 is strongly expressed in IECs of inflamed mucosa, in which neoplastic lesions progressively developed, including adenomas and adenocarcinomas, showing a marked netrin-1 expression at immunohistochemical examination. 23 Furthermore, strong netrin-1 expression appears to be a characteristic feature of neoplastic lesions found in human IBD. A strong expression of netrin-1 is detected in epithelial cells of IBD patients, especially in areas of inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation